Estudio de pre-factibilidad para la instalación de una planta productora de envases de plástico pet clamshell para frutas en el canal moderno de distribución del mercado local - Flores Matallana, Jessica Lorena (2017)
This Project aims to present a pre-feasibility study for the installation of a pet clamshell production plant for fruits in the modern channel, where the technical, economic-financial and market viability is evaluated. This product seeks to promote the sale in small entrepreneurs of the fruit industry. Packaging within the fruit industry allows the development of new markets, so it is important to have a correct design, correctly apply materials that are involved in the manufacture of these and get a quality packaging because they have a direct impact on the chain of distribution by providing a fresh product to the consumer and reducing the losses of the company. The technological advances have allowed to have different types of packaging for fruits such as vacuum packaging, modified atmosphere, boxes, meshes, bags, among others that allow handling, transport and display of these fresh products. The presentation of the fruit causes an impact on the consumer, so it must offer high visual standards and the supermarkets in Peru know about it. Peruvian supermarkets are efficient in their display and ordering, giving customers packed presentations in different portions from the single piece up to 2 kilos, manageable and intended for small spaces, protecting and exhibiting the fruit. The clamshells are one of the packages that allows greater protection during distribution. On the other hand, it is currently a trend in the outlets since it is a rigid container that protects the fruit from handling and can visualize the state of this at all times.